Investigating the Sensitivity of Electric Vehicle Out-of-Home Charging Demand to Changes in Light-Duty Vehicle Fleet Makeup and Usage: A Case Study for California 2030. Issue 10 (October 2021) - Davis, Adam Wilkinson; Tal, Gil
Accurately predicting the spatial distribution and charging demand of future electric vehicles (EVs) is vital to directing investment in charging infrastructure and planning policy interventions. To date, this expansion has been heavily concentrated in wealthy cities and suburbs, among commuters, and among households able to charge their vehicles at home. The expansion of EV ownership will include both changes in where the vehicles are owned and how they are used and charged. This paper demonstrates methods to predict where the expansion of EV ownership is most likely to occur under current market characteristics and allows for testing of scenarios of future characteristics. These methods are demonstrated with an analysis of California, U.S., using a scenario of 4 million battery electric vehicles (BEVs) and 1 million plug-in hybrid electric vehicles (PHEVs), to match the state's goal of 5 million zero-emission vehicles by 2030. These projections are combined with a model for charging behavior to generate scenarios of demand for charging away from home under various fleet characteristics and identify areas of the state with the greatest need for infrastructure investment.